Lymphoma Involving the Heart: A Case Report - Tabbah, Randa; Nohra, Elissar; Rachoin, Rachoin; Saroufim, Kabalan; Harb, Bassam (Frontiers in Cardiovascular Medicine, 2020)
Background: We describe a rare case of cardiac malignancy that counts for less than 1% of the primary cardiac tumors with a poor prognosis. Case summary: It’s a rare case of a primary cardiac lymphoma in a 59 years old patient who presented for recurrent pleuropericarditis with low grade fever and night sweats. Investigations revealed an infiltrating mass in the right atrioventricular groove involving the right atrium and the right ventricular free wall. Pathology confirmed the diagnosis of Non-Hodgkin lymphoma. Chemotherapy with R-CHOP regimen was a success but the patient suffered from recurrence with a complete remission after a second chemotherapy cycle. He was a candidate for bone marrow transplant to reduce other possible relapses. Discussion: Early diagnosis is better for long term prognosis and improve quality of life.